Increasing Lecturing Logic-Based Learning Improves Listening Skills - Dedi Heryadi; Ristina Siti Sundari (Randwick International of Education and Linguistics Science Journal, 2022)
The purpose of this study is to investigate a logical-based learning order and its effects on the growth of pupils lecturing the listening skill. The first approach employed in this study is R&D. Furthermore, data was gathered through inspection, observation, and interviews. The study was conducted for students in the first semester of the 2021/2022 academic year at Siliwangi University Tasikmalaya's Faculty of Teacher Training and Education. The information was quantitatively processed. The findings revealed that logic-based learning syntax positively influenced student lecturing and listening skills. It is advised that the research be followed up and confirmed by people in the same profession to stretcher the research results.